Weed growth and dry matter partition under water restriction - Lima, M.F.P.; Dombroski, J.L.D.; Freitas, F.C.L.; Pinto, J.R.S.; Silva, D.V. (Planta Daninha, 2016)
The capacity of a weed to adapt to the restriction of growth factors is directly related to its ability to compete for those resources with the cultivated species. An experiment was conducted to evaluate the effect of water restriction on the growth and biomass partitioning of four species of weeds. The experimental design used randomized blocks, with five replications. The treatments were arranged in a 4 x 2 factorial, with the first factor being the weed species (Waltheria indica, Crotalaria retusa, Cleome affinis and Commelina benghalensis) and the second, two water regimes: daily irrigation (Irr) and water restriction (WR). The number of leaves, leaf area, dry mass of the plant and its parts (root, stem and leaf), and the mass distribution among different organs (roots, leaves and stems) were determined. The water deficit in the soil increased the root dry matter for C. retusa, W. indica and C. benghalensis, however, it did not alter the mass of the stem of the weeds. C. retusa and W. indica suffered a reduction on the number of leaves, leaf area, dry matter of the leaves and the plant dry matter under water deficit. W. indica and C. retusa had a reduction on the percentage of biomass allocated to the leaves, and an increment on the percentage of the roots mass, while C. benghalensis and C. affinis had an increase only on the roots mass.

A capacidade de uma planta daninha para se adaptar à restrição de fatores de crescimento está diretamente relacionada à sua habilidade de competir por esses recursos com as espécies cultivadas. O experimento foi realizado para avaliar o efeito da restrição hídrica sobre o crescimento e partição de biomassa de quatro espécies de plantas daninhas. O delineamento experimental foi em blocos casualizados com cinco repetições. Os tratamentos foram arranjados em esquema 4 x 2, com o primeiro fator sendo as espécies de plantas daninhas [malva-branca (Waltheria indica), crotalária (Crotalaria retusa), mussambê (Cleome affinis) e trapoeraba (Commelina benghalensis)] e o segundo, dois regimes hídricos: irrigação diária (Irr) e restrição hídrica (Def). Determinou-se o número de folhas, a área foliar, a massa da matéria seca de raiz, caule, folha e total e a distribuição percentual de massa entre os diferentes órgãos (raízes, folhas e caule). O déficit hídrico no solo aumentou a matéria seca das raízes da C. retusa, W. indica e C. benghalensis, porém não alterou a matéria seca do caule das plantas daninhas. C. retusa e W. indica tiveram redução no número de folhas, área foliar, matéria seca das folhas e total em condições de déficit hídrico. W. indica e C. retusa reduziram percentualmente a biomassa alocada nas folhas e aumentaram a de raízes, enquanto a trapoeraba e C. affinis aumentaram somente nas raízes.
Keywords: Waltheria indica; Crotalaria retusa; Cleome affinis; Commelina benghalensis; Soil water deficit